The Future of Corporate Reporting: Integrated Reporting - Sarıoğlu, Mert; Dalkılıç, Ali Fatih; Durak, Mustafa Gürol (International Journal of Contemporary Economics and Administrative Sciences, 2019)
In the today’s business world, it is inevitable to be affected by the rapid changes in terms of companies. Without doubt that the current reporting practices have been impressed by changes as well. Though all stakeholders want to be informed more in a simplest way, many stand-alone and genuinely long reports have been still prepared by companies to demonstrate their financial and non-financial outcomes. However, it is inadequate to assess them separately to see entire story. Additionally, creating value side of current reports are still being debated. Therefore, corporate reporting must move a step forward to express more with less, which called as “Integrated Reporting” (IR) that combines the all pieces of puzzle. It isn’t only integrated both financial and non-financial knowledge into a single and brief report, but also integrated thinking of all aspects of businesses in terms of creating value over time. Accordingly, the aim of this study is to emphasize advancements in corporate reporting towards the IR. Also, it aims to explain its meaning, main aspects, and effect on the business environment. Today, companies should comply with IR, and this study is essential to contribute to the literature, subsequent studies, and companies and organization. Keywords: Corporate Reporting, Integrated Reporting JEL Classification Codes: M40, M49